2004
DOI: 10.1111/j.1467-2494.2004.00242_2.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermatological study on dark eye circles and their treatment with newly developed cosmetics

Abstract: Blood flow stagnation is said to be an important factor for the incidence of dark eye circles, but there are few reports, which have studied dark eye circles and the relationship to blood flow. We have examined dark eye circles dermatologically using a non‐invasive method and made clear the factor related to it. We have also studied the effect of newly developed cosmetics on improvement of dark eye circles. Melanin and haemoglobin content, haemoglobin oxygen saturation and blood flow rate were measured to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Hyperpigmentation and stasis of the eyelids have been considered as possible causes of DCLE, in addition to accentuated shadows created by complex light reflection from a concave, sunken orbital area (1). Anti-DCLE cosmetics have thus generally been designed to improve blood circulation and/or reduce melanin (8). In addition to both quality and quantity of hemoglobin in lower eyelid skin, dermal thickness is likely to be involved in the appearance of DCLE, as our experiments using an in vitro model showed that reflectance of the model increased when the collagen gel layer over the blood layer became thicker (2).…”
Section: Discussionmentioning
confidence: 84%
“…Hyperpigmentation and stasis of the eyelids have been considered as possible causes of DCLE, in addition to accentuated shadows created by complex light reflection from a concave, sunken orbital area (1). Anti-DCLE cosmetics have thus generally been designed to improve blood circulation and/or reduce melanin (8). In addition to both quality and quantity of hemoglobin in lower eyelid skin, dermal thickness is likely to be involved in the appearance of DCLE, as our experiments using an in vitro model showed that reflectance of the model increased when the collagen gel layer over the blood layer became thicker (2).…”
Section: Discussionmentioning
confidence: 84%
“…As for the role of melanin pigmentation, use of a Q-switched ruby laser (694 nm) reportedly improved dark circles in 17 subjects (11). Concerning circulation in the eyelids, Masuda et al (12) reported that mean oxygen saturation of cutaneous blood was lower in subjects with DCLE than in subjects without. When skin temperature falls, the amount of cutaneous blood decreases because blood vessels in the skin contract.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate DCLE in terms of relationships with the accumulation of melanin and hemoglobin, these EI and MI meters are likely to be more suitable for the purpose than a colorimeter. In practice, Masuda et al (12) reported that subjects with DCLE showed larger amounts of both melanin and hemoglobin in the lower eyelids than subjects without DCLE, when measuring these chromophores using a portable reflectance spectrophotometer. However, such reports remain few in number (12,16).…”
Section: Discussionmentioning
confidence: 99%
“…Dark circles under the eyes are a primary feature indicating fatigue and stress [9], however, we found no statistically significant change in the L* value under the eyes although there was a trend toward lower values. Blood flow stagnation contributes significantly to the development of dark circles beneath the eyes [36], and this could account for the decreased skin blood flow that we found under the eyes. Our skin blood flow results could be related to other studies as well that showed increase in skin blood flow during sleep [37].…”
Section: Discussionmentioning
confidence: 71%